Use of 5-Fluorouracil for Management of the Thick-Skinned Nose - Irvine, Leslie E.; Nassif, Paul S. (Facial Plastic Surgery, 2018)
Patients with a thick nasal skin and soft tissue envelope can have unpredictable results and irregular scarring after rhinoplasty surgery. These patients typically have sebaceous tissue over the nasal tip and are particularly susceptible to soft tissue polly beak formation and excess scar tissue in the radix, tip, and septum. Targeted injections of 5-fluorouracil alone or mixed with low concentrations of steroid can be useful to prevent and treat excess postoperative scar tissue deposition. Ideally, four to six injections are performed every 1 to 4 weeks beginning 1 week postoperatively. The injections are most beneficial when performed within the first 3 months after surgery. Even a single injection may improve outcomes with minimal side effects.
Keywords: rhinoplasty; thick skin; 5-fluorouracil; polly beak